On the associations between physical activity and quality of life: findings from an Australian nationally representative panel survey - del Pozo-Cruz, Jesus; Perales, Francsico; del Pozo-Cruz, Jose; del Pozo-Cruz, Borja (My University, 2012)
The purpose of this study is to provide a comprehensive analysis of the associations between the frequency of moderate or vigorous physical activity (MVPA) and quality of life (QoL) measures using longitudinal data and panel regression models on a large, representative sample of the Australian population. This study used yearly panel data on over 23,000 individuals collected by the Household, Income and Labour Dynamics in Australia Survey between 2001 and 2011. Ordinary least squares and fixed effects regression models were used to examine the associations between the weekly frequency of MVPA and several indicators of QoL, including both measures of health-related QoL (such as those derivable from the SF-36) and global subjective well-being assessments (such as self-reported life satisfaction), controlling for observable and unobservable factors. Our results provided consistent evidence that the frequency of MVPA is related to QoL and proved to be robust. A higher frequency of MVPA was related to higher scores in each of the outcomes analysed and using either of two different estimation strategies. The most pronounced associations emerged between the frequency of MVPA and the physical and vitality dimensions of the SF-36. A change from undertaking no MVPA at all to undertaking such activity once a week was remarkably associated with higher QoL. The influence of MVPA on global life satisfaction was only partially channelled through physical and mental health. Conclusion: We provide strong evidence that MVPA is related to QoL, thus adding to the large body of scientific literature demonstrating the benefits of becoming physically active.
Quality of Life Research
Keywords: Health -- Physical activity; Satisfaction -- Life; Health and wellbeing; Satisfaction; Health; Life; Physical activity; Health and wellbeing